Filmless Hospital with PACS as a Workflow Controller, Case Study: National Hospital Surabaya - Romeo Romeo; Febriliyan Samopa (IPTEK Journal of Proceedings Series, 2015)
Traditionally radiology produces a visual representation of medical images in film format for further clinical analysis. While some healthcare providers still used films to display scan results, others are embracing the advancing technology of digital medical images. In radiology, this medical imaging technique is generally equated to filmless radiology. However, modern technology has enabled other clinical areas beyond radiology to use digital imaging, including cardiology, pathology, obstetric and gynecology, orthopedic and dentistry. This widely implementation of filmless system in hospital is known as filmless hospital. This paper discusses filmless hospital using picture archiving and communication system (PACS) as workflow controller as a case study at National Hospital Surabaya.